Racial disparity in tumor microenvironment and distant recurrence in residual breast cancer after neoadjuvant chemotherapy - Gina Kim; Burcu Karadal-Ferrena; Jiyue Qin; Ved P. Sharma; Isabelle S. Oktay; Yu Lin; Xianjun Ye; Saeed Asiry; Jessica M. Pastoriza; Esther Cheng; Nurfiza Ladak; John S. Condeelis; et al. (npj Breast Cancer, 2023)
Abstract Black, compared to white, women with residual estrogen receptor-positive (ER+) breast cancer after neoadjuvant chemotherapy (NAC) have worse distant recurrence-free survival (DRFS). Such racial disparity may be due to difference in density of portals for systemic cancer cell dissemination, called TMEM doorways, and pro-metastatic tumor microenvironment (TME). Here, we evaluate residual cancer specimens after NAC from 96 Black and 87 white women. TMEM doorways are visualized by triple immunohistochemistry, and cancer stem cells by immunofluorescence for SOX9. The correlation between TMEM doorway score and pro-metastatic TME parameters with DRFS is examined using log-rank and multivariate Cox regression. Black, compared to white, patients are more likely to develop distant recurrence (49% vs 34.5%, p = 0.07), receive mastectomy (69.8% vs 54%, p = 0.04), and have higher grade tumors (p = 0.002). Tumors from Black patients have higher TMEM doorway and macrophages density overall (p = 0.002; p = 0.002, respectively) and in the ER+/HER2- (p = 0.02; p = 0.02, respectively), but not in the triple negative disease. Furthermore, high TMEM doorway score is associated with worse DRFS. TMEM doorway score is an independent prognostic factor in the entire study population (HR, 2.02; 95%CI, 1.18–3.46; p = 0.01), with a strong trend in ER+/HER2- disease (HR, 2.38; 95%CI, 0.96–5.95; p = 0.06). SOX9 expression is not associated with racial disparity in TME or outcome. In conclusion, higher TMEM doorway density in residual breast cancer after NAC is associated with higher distant recurrence risk, and Black patients are associated with higher TMEM doorway density, suggesting that TMEM doorway density may contribute to racial disparities in breast cancer.